2022
DOI: 10.1073/pnas.2121513119
|View full text |Cite
|
Sign up to set email alerts
|

Tas2R activation relaxes airway smooth muscle by release of Gα t targeting on AChR signaling

Abstract: Both chronic obstructive pulmonary disease (COPD) and asthma are severe respiratory diseases. Bitter receptor–mediated bronchodilation is a potential therapy for asthma, but the mechanism underlying the agonistic relaxation of airway smooth muscle (ASM) is not well defined. By exploring the ASM relaxation mechanism of bitter substances, we observed that pretreatment with the bitter substances nearly abolished the methacholine (MCh)-induced increase in the ASM cell (ASMC) calcium concentration, thereby suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In addition, the critical findings were observed regardless of whether the HASM had been cotreated with G q -receptor agonists, which constrict the airway. Thus, the idea that TAS2R agonists signal to relaxation strictly by “competitive” mechanisms with G q -receptor actions ( 31 ) seems less likely, at least in human airway SM. Indeed, in prior work we showed that relaxation of human airway rings, and isolated HASM, was readily observed under resting (nonstimulated) conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the critical findings were observed regardless of whether the HASM had been cotreated with G q -receptor agonists, which constrict the airway. Thus, the idea that TAS2R agonists signal to relaxation strictly by “competitive” mechanisms with G q -receptor actions ( 31 ) seems less likely, at least in human airway SM. Indeed, in prior work we showed that relaxation of human airway rings, and isolated HASM, was readily observed under resting (nonstimulated) conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in prior work we showed that relaxation of human airway rings, and isolated HASM, was readily observed under resting (nonstimulated) conditions. Interestingly, in a recent report with mice, gustducin expression was detected in the mouse airway SM, and when deleted the TAS2R-evoked bronchodilation was lost ( 31 ). We find in HASM that this function is likely performed by G i1,2,3 ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, TAS2R46 is a poorly expressed receptor in ASM cells [ 8 , 14 ] compared to the most studied subtypes, but the high specificity and high affinity of absinthin allows the dissection of the role played by this receptor in bronchodilation [ 15 ]. In support of this evidence, Zhou and colleagues [ 69 ] recently demonstrated that the calcium increase following TAS2R activation is not sufficient to determine the phosphorylation of the myosin chain [ 69 ] and thus to trigger ASM cell contraction. Another relevant feature of TAS2Rs is their specificity and selectivity towards the contracting stimulus.…”
Section: Type 2 Taste Receptors In the Respiratory Systemmentioning
confidence: 99%
“…Altogether, this also suggests that TAS2Rs might behave differently in resting or activated cells and that some of the controversies in the literature may be explained by this. It has been observed that TAS2R signaling interferes with the IP3-mediated contraction pathway, lowering cytosolic calcium concentrations to a level no longer sufficient to support the contraction [ 15 , 67 , 69 ]. For example, we have recently shown that the specific TAS2R46 agonist absinthin does not perturb intracellular calcium in resting ASM cells but instead counteracts the increase in cytosolic calcium when the cells are challenged with histamine.…”
Section: Type 2 Taste Receptors In the Respiratory Systemmentioning
confidence: 99%
See 1 more Smart Citation